Why working from home varies across countries and people - Pablo Zarate; Jose Maria Barrero; Nicholas Bloom; Steven J. Davis; Mathias Dolls; Cevat Giray Aksoy (Proceedings of the National Academy of Sciences, 2025)
We investigate why work from home (WFH) rates vary so widely across countries using the Global Survey of Working Arrangements (G-SWA). Conducted in late 2024 and early 2025, G-SWA is the only harmonized international survey of remote work, covering 14,427 full-time, college-educated workers across 37 countries. Our analysis finds that cultural individualism accounts for 29 percent of the cross-country variation in WFH rates—more than any other single factor. Industry structure, population density, and economic development account for smaller shares of the cross-country variation. We conclude with brief remarks on the broader role of culture in shaping the future of work and its implications for labor market policy.